Report of the Working Group on Rural Poverty Alleviation Programmes for the Tenth Five Year Plan (2002-2007) - Planning Commission (Planning Commission, 2001)
The Planning Commission, vide their letter No. M-12018/1/2000-RD dated December 15, 2000 constituted a Working Group under the Chairmanship of Secretary, Rural Development, Government of India on Poverty Alleviation Programmes for the formulation of the 10th Five Year Plan for the Country. The Members of the Group comprised of Government functionaries dealing with rural development and poverty alleviation Programmes both from the Centre and the States, experts and academicians in the field. RBI, NABARD, RMK and reputed NGOs. Smt. Nirmala Buch, former Secretary in the Ministry of Rural development, Shri Mohan Kanda Additional Secretary, D/o Land Resources, Dr. J. S. Sarma, Joint Secretary (RC), and Secretary (RD), Government of Tamil Nadu, were later on co-opted as members of the Group by the Chair
Government of India, Planning Commission
Government of India, Planning Commission